2010
DOI: 10.1038/sj.bjc.6605977
|View full text |Cite
|
Sign up to set email alerts
|

Replication study of SNP associations for colorectal cancer in Hong Kong Chinese

Abstract: Background:Recent genome-wide association studies of colorectal cancer (CRC) have identified common single-nucleotide polymorphisms (SNPs) mapping to 10 independent loci that confer modest increased risk. These studies have been conducted in European populations and it is unclear whether these observations generalise to populations with different ethnicities and rates of CRC.Methods:An association study was performed on 892 CRC cases and 890 controls recruited from the Hong Kong Chinese population, genotyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 27 publications
(36 reference statements)
9
52
2
2
Order By: Relevance
“…By contrast, this association was not significant in our subjects. For rs10795668, located on 10p14, there was no significant association with CRC risk, but its protective effect was similar to that described in previous studies [4,10,15] . Furthermore, this SNP was shown to be associated with CRC in a northern Chinese population [9] but not in our subjects.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…By contrast, this association was not significant in our subjects. For rs10795668, located on 10p14, there was no significant association with CRC risk, but its protective effect was similar to that described in previous studies [4,10,15] . Furthermore, this SNP was shown to be associated with CRC in a northern Chinese population [9] but not in our subjects.…”
Section: Discussionsupporting
confidence: 70%
“…However, all of these studies were conducted in Caucasians, with only one replicated in a Japanese population [5] . More recently, the association between several loci identified in GWAS for CRC was confirmed in a northern Han Chinese population [9] and in Hong Kong Chinese [10] Subjects . Here, we examined the impact of 11 previously reported loci in a Han Chinese population in Jiangxi Province, Southern China.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, Slattery M.L., et al couldn't find any significant association between rs4464148 and CRC susceptibility even when laminated them by age, tumor site or family history (Slattery et al, 2010). Furthermore, in two distinguished researches that have been investigated in Asia, same results have been accomplished (Ho et al, 2011;Li et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…To the best of our knowledge, several studies corroborated the role of rs12953717 polymorphism in cancer susceptibility (Broderick et al, 2007;Tomlinson et al, 2008;Curtin et al, 2009;Middeldorp et al, 2009;Pittman et al, 2009;Slattery et al, 2010;Ho et al, 2011;Li et al, 2011). According to previous cancer-susceptibilitystudies which mainly revealed the remarkable association between the SMAD7 SNP and the risk of CRC, our study demonstrated that allele T at rs12953717 can increase the risk of CRC.…”
Section: Discussionsupporting
confidence: 53%